Induction of DNA damage and apoptosis in Saccharomyces cerevisiae by a yeast killer toxin - Klassen, Roland; Meinhardt, Friedhelm (Cellular microbiology, 2005)
Summary The cellular response of Saccharomyces cerevisiae to a linear plasmid encoded killer toxin from Pichia acaciae was analysed. As for the Kluyveromyces lactis zymocin, such toxin was recently shown to bind to the target cell's chitin and probably acts by facilitating the import of a toxin subunit. However, as distinct from zymocin, which arrests cells in G1, it provokes S‐phase arrest and concomitant DNA damage checkpoint activation. Here, we report that such novel toxin type causes cell death in a two‐step process. Within 4 h in toxin, viability of cells is immediately reduced to approximately 30%. Elevated mutation rates at the CAN1 locus prove DNA damaging mediated by the toxin. Cells arrested artificially in G1 or G2/M are very rapidly affected, while cells arrested in S loose their viability at a slower rate. S‐phase arrest is, thus, a response of target cells to cope with DNA damage induced by the toxin. A second decline in viability requiring metabolically active target cells emerges upon toxin exposure over 10 h. During this phase, toxin treated cells develop abnormal nuclear morphology and react positive to terminal deoxynucleotidyl transferase‐mediated nick end‐labelling (TUNEL), indicative of DNA fragmentation. Furthermore, as judged from staining with fluorescein conjugated annexinV, cells expose phosphatidylserine at the outer membrane face and the formation of reactive oxygen species (ROS) is increased. ROS formation and concomitant cell death was heavily suppressed in a rho‐ derivative of the tester strain, while immediate reduction of viability was indistinguishable from the wild type. As a strain lacking the cellular target because of defects in the major chitinsynthase (Chs3) did not display such characteristic changes, the chitin binding and DNA‐damaging P. acaciae toxin constitutes an apoptosis inducing protein. Both, DNA‐damaging and apoptosis induction are unique features of this novel toxin type.